2018
DOI: 10.1186/s12887-018-1282-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient air pollutants and preterm birth in Ningbo, China: a time-series study

Abstract: BackgroundExposure to air pollutants has been related to preterm birth, but little evidence can be available for PM2.5, O3 and CO in China. This study aimed to investigate the short-term effect of exposure to air pollutants on risk preterm birth during 2014–2016 in Ningbo, China.MethodsWe conducted a time-series study to evaluate the associations between daily preterm birth and major air pollutants (including PM2.5, PM10, SO2, NO2, O3 and CO) in Ningbo during 2014–2016. A General Additive Model extend Poisson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Spearman's correlation coefficients were used to estimate the correlations between temperature, RH and air pollutants. 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spearman's correlation coefficients were used to estimate the correlations between temperature, RH and air pollutants. 24…”
Section: Discussionmentioning
confidence: 99%
“…Daily temperature (°C) and RH (%) were obtained from the National Weather Data Sharing System (https://data.cma.cn/). Spearman’s correlation coefficients were used to estimate the correlations between temperature, RH and air pollutants 24 …”
Section: Methodsmentioning
confidence: 99%
“…Air pollution exposure increases the risk of PTB28 29 and black Americans are more highly exposed due to residential proximity to industrial facilities,30 traffic31 and other sources. One recent study of over 37 000 births in China demonstrated that as IQR of short-term exposure to gases (SO 2 and NO 2 ) and particulate matter (<2.5 [PM 2.5 ] microns and <10 [PM 10 ] microns in diameter) increased, the odds of PTB were 3.7–6.5 times higher 32…”
Section: Macroenvironmental Factors That May Help To Explain Racial Dmentioning
confidence: 99%
“…Multiple studies have shown that SO 2 exposure had the strongest correlation with shortening pregnancy [ 29 ], and the result of a series of studies in other countries reported that NO 2 exposure increased the risk of preterm birth more significantly than particulate matters [ 30 ], which is consistent with our results. However, one study reported that the risk of preterm birth increased by 4.84% for each IQR increase in PM 2.5 exposure, while the ER (Excess risks) of SO 2 was 3.65% [ 31 ]. Another research study observed a significant association between NO 2 exposure and preterm birth only at the end of pregnancy [ 22 ], and a natural experiment study even showed that PM 10 and NO 2 were both not significantly associated with preterm birth [ 32 ].…”
Section: Discussionmentioning
confidence: 99%